Information Technology and Capacity Source Power Man for Agency Performance Improvement Government: Evidence from Minahasa, Indonesia - Dondokambey, Robby; Tuerah, Philoteus; Mandagi, Marthinus (International Journal of Information Technology and Education, 2022)
Embodiment good governance required source power man apparatus government owns competence in maintenance governance and development. The study aims to analyze the influence source power humans and information technology to enhance the performance of government. Method research used studies quantitative type ex post facto research with a sample respondent as many as 30 respondents. The study was conducted within the government secretariat district Minahasa. Research results from this showing that there is a significant influence among source power humans and improved performance of government. Studies also find that there is a strong influence among the use of information technology and improve performance government and influence positive and significant HR Capacity and IT Mastery together to performance Employee. Studies conclude that Some companies not only need Adequate HR capacity good but good or even very good so that could produce a good and helpful employee performance company for reach purposes. Good IT mastery will push employees to work with more passion and more good again so that the results achieved will also be good.